PENGARUH RASIO KEUANGAN DAN KAPITALISASI PASAR TERHADAP TINGKAT PENGEMBALIAN SAHAM - Achmad Faisal Yunianto; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2023)
This research was conducted to see the influence of financial ratios in the form of price to equity ratio, earnings per share and debt to equity ratio and to see the influence of market capitalization on stock market returns. The population in this research is all companies included in the KOMPAS100 index in the 2019-2021 period. Samples were taken using the purposive sampling method. The total sample is 55 companies with a total of 124 data. Multiple regression analysis is used in testing research hypotheses. The results of this research show that all the variables in this research have no influence on stock market returns.